Radioisotope scan of the liver - Gaudiano, Javier (Cirugía del Uruguay, 1982)
The value of scintiraphy for liver exp!oration by means of radiocolloid liver scintigraphy, liver blood Pool scintigra. phy, colescinigraphy and Gallium-citrate scintigraphy is discussed. Radiocolloid Jiver scintigraphy and Jive, blood pool scintigraphy are useful in the dianosis of hydatic disease. in the search of liver methastases, in traumatic lesiones of he Jiver, in primary liver tumors, in cirrhosis, in the diagnosis of Jiver abscesses and of abscesses lying etween liver and diaphragma. The value of scintiraphy for liver exp!oration by means of radiocolloid liver scintigraphy, liver blood Pool scintigraphy, colescinigraphy and 67 Gallium-citrate scintigraphy is discussed. Cholescin igraphy is a vauable too! n he study of the biliary ract diseases and above all for the dianosis of acute cholecistytis. 67 Ga-citrate sciniraphy is a good complementary procedure for the study of Jiver abscesses and above all for the search of abscesses following biliary tract an liver surgery.